Poly(vinylidene fluoride) separators for next‐generation lithium based batteries. Issue 12 (12th May 2021) - Liu, Rong; Yuan, Botao; Zhong, Shijie; Liu, Jipeng; Dong, Liwei; Ji, Yuanpeng; Dong, Yunfa; Yang, Chunhui; He, Weidong
Abstract: Lithium‐ion batteries (LIBs) have become star products in wireless electronic equipment, new energy vehicles and many other fields due to their advantages of high energy density, light weight, good stability, high charging‐discharging efficiency, long service life and environmental friendliness. The separator is an indispensable part of batteries that does not participate in electrochemical reactions, separating the anode and cathode. It has a microporous structure, which can store electrolyte and allow ions to transfer freely. Poly(vinylidene fluoride) (PVDF)‐based separators are characterized by strong polarity, high dielectric constant, stable electrochemical performance, excellent tensile properties and mechanical strength, favorable thermal stability and wettability. Therefore, they are proposed to be potential candidates for novel separators in the field of LIBs. This review introduces the recent researches and advances in PVDF‐based separators for LIBs, with the characterizations and requirements for separators. It is mainly divided into the two types including monolayer and multilayer separators. Furthermore, the performance of the PVDF‐based separators is summarized, and the challenges and prospects in their practical application are briefly analyzed. Abstract : PVDF‐based separators are considered to have great potential in the field of lithium‐based batteries. In this paper, the recent advances of PVDF separators for lithium‐based batteries are reviewed. The preparation, structure and performances of PVDF‐based separators are discussed as well. In view of the existing problems and challenges, the improvement direction in practical application is briefly analyzed.